Design of Solid Tire Power Screw Press Machine. - Wabwire, Ebenezer Emmanuel (Kabale University, 2025)
This research study aspects and findings of a study focused on the design of a solid tire power screw press machine that employs a nut and screw mechanism to apply force. The purpose of the report is to provide a concise summary of the research conducted and the main outcomes achieved. Chapter One introduces the study, offering a brief background on solid tire press machines, the problem being addressed, the project’s scope, and its objectives both general and specific. Additionally, it discusses the research questions, justification, significance, and limitations of the project. The primary issue addressed is the inefficiency and delays associated with existing manually operated machines for dislodging solid tires. The study aims to design a power-driven machine to improve performance and overcome these challenges. Specific objectives include conceptualizing dislodging methods, selecting and sizing components, defining design specifications, developing conceptual designs, and detailing the chosen design through working drawings. Chapter Two provides a literature review on solid tire dislodging techniques and the design of solid tire power screws. Chapter Three describes the methodology used in designing the machine, including identifying customer requirements, explaining the machine's operating principles, and developing a layout using SOLIDWORKS software. The machine operates by powering a motor that drives the pinion gear, which rotates the driven gear and worm gear. This action creates axial force via the integrated nut and power screw, dislodging the tire on the bench. Once dislodging is complete, the motor is switched off, and the tire and rim are removed by the operator. The process can then be repeated for additional tires.